(untitled) (Research, Society and Development, 2021)
In this study, processed cheese was produced with a total and partial substitution of xanthan gum by Moringa seed extract and stored at 4ºC. Chemical composition pH, acidity, color, texture, and rheology were studied. The chemical composition differed significantly (p <0.05) between the samples. Protein content was higher for the sample containing only Moringa extract. The acidity differed significantly (p <0.05) only on the last day of storage. The pH values ​​remained within the established quality limits (pH≥6.0) for all samples during the 21 days of storage. The addition of extract affected the color and microstructure of the samples; processed cheese with added extract showed smaller particle size fat globules and distributed without uniformity. The Moringa extract interfered in the texture of the product, proving to be a great partial and/or total substitute of chemical preservatives. The sample with greater gum substitution by the Moringa extract had hardness equal to the control sample. Also, this sample (T4 - 0.15% gum and 0.35% Moringa extract) presented higher consistency index (K). Samples did not show significant differences during storage period for cohesiveness. The rheological profile showed that all samples presented a non-Newtonian (pseudoplastic) profile. Thus, it is believed that the Moringa seed has a potential for use as a thickener substitute.